Playful Identities The Ludification of Digital Media Cultures - de Lange, Michiel; Raessens, Joost; Frissen, Valerie; Lammes, Sybille; de Mul, Jos (MediaMatters, 2015)
In this edited volume, eighteen scholars examine the increasing role of digital media technologies in identity construction through play. Going beyond computer games, this interdisciplinary collection argues that present-day play and games are not only appropriate metaphors for capturing postmodern human identities, but are in fact the means by which people create their identity. From discussions of World of Warcraft and Foursquare to digital cartographies, the combined essays form a groundbreaking volume that features the most recent insights in play and game studies, media research, and identity studies.